Determinants of shariah non-compliant events in Islamic banks in Malaysia: With special reference to tawarruq-based - Ali, Mohammad Mahbubi; Hassan, Rusni (International Islamic University Malaysia, 2016)
Tawarruq is a new phenomenon in the Islamic financial landscape. It has gained wide acceptance from the market due to its inherent characteristics that can offer similar features as the conventional structure. Nevertheless, tawarruq is exposed to a high degree of shari’ah non-compliant risk mainly because it involves a series of sale contracts in succession. The present study investigates the determinants of shari’ah non-compliant events (SNEs) in tawarruq-based financing as practiced by Islamic banks in Malaysia. The study adopts the Analytic Network Process (ANP) gathering different views of experts from practitioners, regulators, sharī’ah scholars/advisors and researchers/academicians. The study found that lack of understanding and knowledge, inadequate control mechanism and reporting, ineffective functional structure, incompatibility of system to the execution of Islamic products, improper document execution and sequence, and inadequate internal policies and governing rules are the key determinants of SNEs in tawarruq-based financing in Islamic banks in Malaysia.